2018
DOI: 10.1007/s10548-018-0692-1
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Evoked and Non-evoked Functional Networks

Abstract: The growing interest in brain networks to study the brain’s function in cognition and diseases has produced an increase in methods to extract these networks. Typically, each method yields a different network. Therefore, one may ask what the resulting networks represent. To address this issue we consider electrocorticography (ECoG) data where we compare three methods. We derive networks from on-going ECoG data using two traditional methods: cross-correlation (CC) and Granger causality (GC). Next, connectivity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 57 publications
(75 reference statements)
2
20
0
Order By: Relevance
“…Next, based on connectivity analysis of ER networks (Hebbink et al, 2019;van Blooijs et al, 2018), we concluded that DRs are indirect responses to the stimulation. Model simulations show that they may arise from feedforward propagation of ER activity and notably projections to inhibitory populations that normally restrain neural activity.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Next, based on connectivity analysis of ER networks (Hebbink et al, 2019;van Blooijs et al, 2018), we concluded that DRs are indirect responses to the stimulation. Model simulations show that they may arise from feedforward propagation of ER activity and notably projections to inhibitory populations that normally restrain neural activity.…”
Section: Discussionmentioning
confidence: 94%
“…We use the detected ERs to construct a network representing effective connectivity (Entz et al., ; Hebbink et al., ; Keller et al., ; van Blooijs et al., ). Each electrode represents a node in this network.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations